Fabrication of La2Zr2O7 ceramic fibers via electrospinning method using different La2O3 precursors. Issue 15 (15th November 2016) - Yuan, Kangkang; Feng, Cong; Gan, Xinzhu; Yu, Zhichao; Wang, Xinqiang; Zhu, Luyi; Zhang, Guanghui; Xu, Dong
Abstract: Despite La2 Zr2 O7 ceramic fiber has been fabricated by electrospinning method, the effects of thermal pyrolysis process on the microstructures and properties of the fibers have seldom been considered. Three La2 O3 precursors were used to prepare La2 Zr2 O7 ceramic fibers. Phase transformation of La2 Zr2 O7 ceramic fibers were characterized by XRD and Raman spectra. The influence of the decomposition process on the microstructure of the fibers was studied by TG/DSC, XPS and SEM. The results show that slow weight loss leads to smaller grain size which could obtain higher strength fibers while fast weight loss could develop pores which are benefit to the decrease of the thermal conductivity.